Is Corruption Control Good for All Businesses? The Role of Cash in the Bribery Game - Nguyen, Bach (Senate Hall, 2019)
This study investigates the distributional effects of corruption on the performance of cash-rich and cash-poor firms. We propose that cash-bribes are the ultimate objective of corrupt officials. Therefore, firm-level cash-flow is one of the most important determinants of corrupt decisions. Analysing a 15-year (2006-2015) panel of 2.4 million firm-year observations in Vietnam, we find that cash-rich firms gain less benefit and that their performance may even be harmed when corruption controls improve (less corruption-related harassment). By distinguishing administration corruption from negotiation corruption, we aim to explain this paradox.
Keywords: corruption|institutions|firm performance|cash brib|Vietnam